Economics of fish production demand and trade in terai region of Nepal - Sapkota, Sudha; Raimajhi, Asha; Sah, Umita; Devkota, Hareram; Tripathi, Shreeya (Journal of Agriculture and Natural Resources, 2024)
Aquaculture is gradually establishing itself as a significant agricultural activity in Nepal, a country endowed with abundant water resources and diverse topography. Despite its potential, aquaculture in Nepal, faces significant challenges that hinders optimal fish production and economic returns. This study was conducted in 2022 to 2023 and aims to analyze the current status of fish farming, examining production trends, socio-economic profiles of fish farming households, cost structures, and profitability. The research highlights the achievements of the Game Changer program, which has significantly boosted fish yield through fry production. It also examines the growth and economic feasibility of fish farming in Siraha, Nepal. Over the past decade, fish production has grown significantly, driven by enhanced aquaculture practices and supportive policies, the sector's profitability is reflected by a Benefit-Cost Ratio (BCR) of 1.28, despite challenges such as high feed costs and reliance on imported seeds. Fingerling production in Siraha experienced remarkable growth, rising from 5.5 million in 2019/2020 to 13.65 million in, 2021/2022 with a Compound Annual Growth Rate (CAGR) of 57.54%. Based on this growth trajectory, fingerling production is expected to reach 37.11 billion by 2034, showcasing the sector’s significant potential for expansion. Despite notable progress, several constraints such as limited technical knowledge, inadequate access and knowledge to quality inputs, and insufficient market infrastructure persist. This study underscores the need for targeted interventions to address these challenges. Recommendations include enhancing technical training, improving low-cost high-quality inputs, strengthening market facilities, promoting gender balance, and advocating for supportive policies. By leveraging these strategies, Nepal can significantly increase its aquaculture production, contributing to national food security, economic growth, and employment generation.